2012
DOI: 10.4103/0970-4388.108929
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental fluorosis in relation with different fluoride levels in drinking water among school going children in Sarada tehsil of Udaipur district, Rajasthan

Abstract: There was an increase in prevalence of dental fluorosis with a corresponding increase in water fluoride content from 0.8 ppm to 4.1 ppm. A significantly strong positive correlation was found between CFI and fluoride concentration in drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…The size of the apatite crystals in the skeletal system is increased due to fluoride. Fluoride incorporation into the skeletal system and dental enamel is dependent on age [92,93]. When the fluoride concentration in drinking water is more than 2 ppm, dental fluorosis begins.…”
Section: Fluoride Health Effectsmentioning
confidence: 99%
“…The size of the apatite crystals in the skeletal system is increased due to fluoride. Fluoride incorporation into the skeletal system and dental enamel is dependent on age [92,93]. When the fluoride concentration in drinking water is more than 2 ppm, dental fluorosis begins.…”
Section: Fluoride Health Effectsmentioning
confidence: 99%
“…[13] These finding are in contrast to the reports by Sarvaiya and coworkers. [8] Smith in 1988 noted that dental caries was declining even in people consuming un-fluoridated water and may be attributed due to sources in the environment such us fertilizers and solid wastes containing fluoride. He also claimed that fluoride containing dental health products might contribute to this excess intake of fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Sarvaiya and coworkers found a very strong correlation between fluorosis index and fluoride levels in drinking water in their study on school children in Rajasthan in 2012. [8] Firempong and co-workers (2013) conducted a study on fluorosis and water fluoride levels in Ghana and found a positive correlation between the two.…”
Section: Research Articlementioning
confidence: 99%
“…In another study conducted by Sarvaiya et al 14 in Sarada Tahsil of Udaipur district in Rajasthan there was a prevalence of 69.84% and increased Community Fluorosis Index with higher water fluoride content.…”
Section: Discussionmentioning
confidence: 99%